1998
DOI: 10.1080/00480169.1998.36045
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age, weaning, drench volume and yarding on ruminoreticulum bypass in sheep, with reference to the anthelmintic efficacy of benzimidazole drenches

Abstract: These results support the use of low volume formulations of benzimidazole drenches for New Zealand pasture-fed lambs less than 6 months old. The results indicate that, in order to obtain the optimum efficacy of benzimidazole anthelmintics in New Zealand pasture-fed sheep, which have been yarded for 24 hours, low volume drench formulations should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…These aspects have been reviewed previously by Hennessy and others (1997) and Sargison and others (1998).…”
mentioning
confidence: 99%
“…These aspects have been reviewed previously by Hennessy and others (1997) and Sargison and others (1998).…”
mentioning
confidence: 99%
“…In adult ruminants, a certain degree of rumen bypass does occur during drinking (but note that the majority of fluid still enters the rumen; Woodford et al 1984). This mechanism has been used repeatedly for the administration of fluid drugs that should ideally bypass the rumen and enter the abomasum directly (Sargison et al 1998;Sargison et al 2000a;Sargison et al 2000b). However, it should be noted that the bypass mechanism originally proposed by Hofmann (1973Hofmann ( , 1989 and investigated in this study is not linked to drinking water intake, but to solid food ingestion, mastication, and the concomitant hypothetical solubilisation of nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In domestic ruminants, radiographic studies after the application of a contrast medium (mostly barium sulfate) have been used (Sargison et al 1998), and a special breath test including the application of a marker isotope and repeated sampling of exhalate has been validated for the study of reticular groove closure (McLeay et al 1988), and groove closure has been tested by measuring serum glucose after feeding a glucose solution (Lousse and Ronsse 1950). In fistulated animals, presence or absence of an ingested marker in the ruminal contents (Waghorn and Shelton 1994) can be used as an indication for groove closure, as well as temperature recording at different sites of the gastrointestinal tract following the application of cold drinking water (Paragon and Hachet 1980), or simple visual or manual inspection of the groove (Hegland et al 1957).…”
Section: Introductionmentioning
confidence: 99%
“…There are many experimental protocols in which it has been demonstrated that treatment with glucose solutions (26,42,(63)(64)(65) , with NSAIDs such as meclofenamate and acetaminophen (37,66,67) , with certain antibiotics such as chloramphenicol (57) or sulfamethoxazole-trimethoprim (50) , and some antiparasitic are generally ineffective due to product degradation by ruminal microflora or, conversely because of too fast circulation through the rumen (68)(69)(70) . It is therefore of great interest to stimulate furrow closure in the first case and suppressing it in the later.…”
Section: Use In Veterinary Medicinementioning
confidence: 99%
“…Other antiparasitics studied by stimulating the reticular groove are benzimidazole (68) , oxfendazole (69) or some coccidiostats as the medium chain fatty acids (MCFAs) (70,78) .…”
Section: Use In Veterinary Medicinementioning
confidence: 99%